Automotive ECU Basic Test & Validation for XIL in ADAS: A Comprehensive Overview on HIL bench phase - Ahmed Alami; Fouad Belmajdoub (EPJ Web of Conferences, 2025)
Nowadays the automotive industry is shifting drastically towards Advanced Driver Assistance Systems (ADAS) and this technology is requiring more and more a robust Test & Verification (T&V) methodology for developing Electronic Control Units (ECUs). It is crucial to ensure the safety and reliability of these embedded systems for both end customers and Original Equipment Manufacturers (OEMs). This involves reducing T&V time, increasing robustness, and improving early fault detection. Hardware-in-the-Loop (HIL) benches play a critical role in early fault detection before the Vehicle Under Test (VUT) phase during ECU validation. This paper outlines a comprehensive T&V strategy for ECU development within the ADAS context, framed by the V- model. It discusses basic test methods workflow used by OEMs on HIL benches and introduces an automated tool for one method of the workflow most exactly for frame error detection, it addresses common errors in communication protocols, diagnostics, ECU flashing, and telecoding. The tool generates test cases based on frame content correctness, in the aim to automate various test scenarios. This work provides practical examples and serves as a ressource for advancing automated HIL T&V methods for ADAS.